1995
DOI: 10.1116/1.587865
|View full text |Cite
|
Sign up to set email alerts
|

Roughness analysis of Si/SiGe heterostructures

Abstract: Atomic force microscopy is used to measure surface morphology of modulation doped Si/SiGe heterostructures. Three components in the surface roughness are observed: μm-scale roughness arising from misfit dislocations formed to relieve strain, 1000-Å-scale roughness believed to be associated with three-dimensional growth of the electron or hole channel layers, and atomic-scale roughness with wavelengths of 10–100 Å. Detailed Fourier spectra of the roughness are obtained and used as input to a scattering computat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 0 publications
2
24
0
Order By: Relevance
“…Our best fits are obtained with ∆ = 1.2-1.5 A and Λ = 40-60Å suggesting good quality interfaces. These IFR parameters are also within the range of values reported in the literature [9,11,12,18] A was also assumed by Leuliet et al in their study of GaAs/AlGaAs QCLs [13], to obtain the best agreement between theoretical and experimental total scattering rates. In all our calculations we also assume the carrier temperature T h at detection time to be related to the lattice temperature T latt according to T h = T latt +δT , where δT is a constant (i.e., T latt -independent) quantity representing the residual effects of the carrier heating produced by the laser pulse.…”
Section: Resultssupporting
confidence: 63%
“…Our best fits are obtained with ∆ = 1.2-1.5 A and Λ = 40-60Å suggesting good quality interfaces. These IFR parameters are also within the range of values reported in the literature [9,11,12,18] A was also assumed by Leuliet et al in their study of GaAs/AlGaAs QCLs [13], to obtain the best agreement between theoretical and experimental total scattering rates. In all our calculations we also assume the carrier temperature T h at detection time to be related to the lattice temperature T latt according to T h = T latt +δT , where δT is a constant (i.e., T latt -independent) quantity representing the residual effects of the carrier heating produced by the laser pulse.…”
Section: Resultssupporting
confidence: 63%
“…At the same time, the values of reported from AFM measurements vary from 10-30 nm [92]. Random 2D surfaces are generated from the corresponding power spectra using a standard 2D Fourier synthesis approach [93]. The "analog" random surface is then quantised in steps to take into account the discrete nature of the interface roughness steps associated with the atomic layers in the crystalline silicon substrate [83].…”
Section: Oxide Thickness Fluctuationsmentioning
confidence: 99%
“…The phases of the elements are selected randomly, ensuring that each surface is unique. Several conditions 16 must be satisfied to ensure that the corresponding 2-D surface in real space, obtained by inverse Fourier transformation, represents a real function, H x y . Figure 7 illustrates how this random surface, H , can be used to assign the dielectric constants to the different materials in the gate oxide.…”
Section: Simulation Methodologymentioning
confidence: 99%
“…Recent studies 37 38 have shown that scattering within the channel continues to affect the I ON current in nano-scale MOSFETs, where the fully ballistic regime is never reached. The simulations were carried out for substrate acceptor concentrations 2 × 10 16 Figure 14; the solid blue curve with the square symbol is obtained excluding the ionised-impurity scattering.…”
Section: Calibration For Siomentioning
confidence: 99%